PENGEMBANGAN MEDIA BELAJAR MONOPOLI MATEMATIKA BUDAYA (MONOMABA) BERBASIS BUDAYA DI SALATIGA UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING DAN RASA CINTA BUDAYA PADA PEMBELAJARAN PERKALIAN MATEMATIKA SISWA KELAS IV SD - Nugraha, Ronan Beema; Kusuma, Dani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve problem-solving abilities and love of culture. This type of research is development research (Research & Development). The subjects in this research were 16 students in class IV-A at SDN Blotongan 02. Data collection was carried out by interviews, observations, and initial ability tests. This research method uses quantitative descriptive. The research results show that Monomaba media can be an alternative for fourth grade teachers to improve students' problem solving abilities and love of culture. The results of the practicality sheet analysis show a percentage of 81.5%, which means it is included in the good category. Media Monomaba obtained a material expert validation score of 90.6 and a media expert validation score of 94.6. Both validation results are in the "Very Good" category. Monomaba media was declared effective because the post-test results increased from the pre-test. If there is a difference in the average results of the post-test and pre-test which is indicated by a significance (2-tailed) of 0.000 <0.05 then Ho is rejected. So it can be concluded that there is a significant influence on the use of Monomaba media. Monomaba media is effectively used as a medium because there is an increase in student posttest results of 0.71 using the N Gain calculation, which is in the high category.